SYMPTOMS OF PAYRA SYNDROME, DIAGNOSIS AND TREATMENT MEASURES - Muxtarova Nargiza Toxirovna; Ganiyeva Shahlo Fayzilloyevna (Web of Journals Publishing, 2026)
Payra syndrome is a congenital condition in which a part of the large intestine, called the "splenic flexure," becomes abnormally bent, causing severe constipation, abdominal pain, bloating, and digestive problems. More common in girls, this syndrome slows down the movement of stool through the intestines, which can often lead to intoxication and other complications.
Keywords: Colon, constipation, barium enema, colonoscopy, drug electrophoresis.